Photonic modulation of EGFR: 280nm low level light arrests cancer cell activation and migration - Botelho, C. M. (2017)
Overexpression of the Epidermal Growth Factor Receptor (EGFR) by cancer cells is associated with a poor prognosis for the patient. For several decades, therapies targeting EGFR have been designed, including the use of monoclonal antibodies and small molecule tyrosine kinase inhibitors. The use of these molecules had good clinical results, although its efficiency (and specificity) is still far from being optimal. In this paper, we present a new approach for a possible new cancer therapy targeting EGFR and using low intensity 280nm light. The influence of 280nm UVB illumination on cancer cells stimulated with 2nM of EGF was followed by time-lapse confocal microscopy. The 280nm illumination of the cancer cells blocks EGFR activation, inhibiting EGFR internalization and cell migration thus inhibiting the transition to the metastatic phenotype. Exposure time is a very important factor. The higher the illumination time the more significant differences were observed: 280nm light delayed or completely halted EGFR activation in the cell membrane, mainly at the cell junction level, and delayed or halted EGFR endocytic internalization, filopodia formation and cell migration.